AN ANALYSIS OF CHARACTER EDUCATION VALUES IN TENTH GRADE ENGLISH TEXTBOOK IN MERDEKA CURRICULUM - Caterine Putri Octavia; Natalia Anggrarini; Atikah Wati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
Character education values ​​play an important role in influencing students to build morale and integrity. This research aims to investigate the character education values contained in the textbook specified in reading text. This research used qualitative method using the content analysis technique to tenth grade English textbook entitled pathway to English. This research used 18 characters education values from Kemendiknas and 3 characters education values from Pancasila Student Profile qualification. The instrument used in data collection is document. Documentation used is the content of textbook specifically in reading text. The result showed that 15 characters education values ​​were found with a total frequency of 57 sentences from 16 reading texts in the textbook entitled Pathway to English. This research implies communicative values, especially in character education values which raises various ideas, issues, facts and stories that contain character values with the aim of being moral education for students. This research suggested other researchers to conduct the research about the technique in integrating character in English textbook.